You're going to love this book! - John, Jory; Tallec, Olivier (New York : Farrar Straus Giroux, 2024)
"Attention, reader: You're going to LOVE this book! No, really, you are. It's got everything you could ever want: comedy, drama, action, heart. Plus--are you ready? It's got homework! Ahh yeah! And a trip to the best place ever, the dentist! Ahhhh yeahhh! Additionally--brace yourself--it's got raisins! Nature's candy. AHH YEAHHH! This book is so great, you won't be able to stop reading it. I DARE you not to have fun"--
"Warning! Occasionally, some readers may have a slightly different opinion"--Cover.
Keywords: Books and reading -- Juvenile fiction; Kangaroos -- Juvenile fiction; Encouragement -- Juvenile fiction; Animals -- Juvenile fiction; Vegetables -- Juvenile fiction; Dentists -- Juvenile fiction; Homework -- Juvenile fiction; Animals -- Fiction; Kangaroos -- Fiction; Books and reading -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Books & Libraries; Books and reading -- Juvenile fiction; Humorous fiction; Books and reading -- Fiction; Pictures; Animal fiction; Picture books